THE EFFECT OF THE “RAYQAL” APPLICATION ON MOTHERS’ KNOWLEDGE, ATTITUDE, AND BEHAVIOR IN STIMULATING TODDLER DEVELOPMENT - Harefa, Umy Darni; Herawati, Yanti; Rachmiatie, Atie; Garna, Herry; Anwar, Anita Deborah; Wijayanegara, Hidayat (Siklus : Journal Research Midwifery Politeknik Tegal, 2025)
Parents need effective media to enhance their knowledge, attitudes, and behaviors in supporting early childhood growth and development. One such tool is the "Rayqal" application, which is designed to help mothers stimulate optimal development in toddlers. This study aimed to analyze the effect of the "Rayqal" application on improving maternal knowledge, attitudes, and behaviors related to toddler development. A quasi-experimental design with a pretest-posttest control group was used. The population consisted of 80 mothers with children aged 0–59 months, selected using a total sampling technique. Data were analyzed using the Mann-Whitney test. Results showed significant differences in knowledge (ρ=0.000), attitudes (ρ=0.000), and behaviors (ρ=0.000) after the use of the "Rayqal" application. Specifically, in the intervention group, behavior scores increased from a pretest mean of 0.65 to a posttest mean of 1.18. These findings indicate that "Rayqal" significantly improved maternal abilities to support child development. In conclusion, the "Rayqal" application positively influences mothers' knowledge, attitudes, and behaviors in stimulating toddler growth. It is recommended that the use of "Rayqal" be expanded to support SDIDTK (Early Detection and Intervention for Child Growth and Development) programs at Gunungsitoli District Health Center to help prevent developmental delays in children.